Answer:
B
Step-by-step explanation:
Ecology is the study of ecosystems. That is, ecology is the study of how living organisms interact with each other and with the nonliving part of their environment.
Answer:
Number of jars can be filled from 15kg of the salt = 468 or 469 jars (Approx.)
Step-by-step explanation:
Given:
Amount of salt containing in jar = 32 gram
Total amount of salt in jar = 15 kg
Find:
Number of jars can be filled from 15kg of the salt
Computation:
Total amount of salt in jar = 15 kg
Total amount of salt in jar (in grams) = 15 x 1000 g
Total amount of salt in jar (in grams) = 15,000 g
Number of jars can be filled from 15kg of the salt = Total amount of salt in jar (in grams) / Amount of salt containing in jar
Number of jars can be filled from 15kg of the salt = 15,000 / 32
Number of jars can be filled from 15kg of the salt = 468.75
Number of jars can be filled from 15kg of the salt = 468 or 469 jars (Approx.)
Answer:
a. Given a number of tablespoons, find the number of cups:
1. Since he needs 2 cups, he can use 2×16=32 tablespoons.
2.Since he needs 1/2 cup, he can use 1/2×16=8 tablespoons.
He needs 1 1/4 cups. 1 cup is 16 tablespoons. 1/4 cup is 1/4×16=4 tablespoons. So altogether he needs 16+4=20 tablespoons.Given a number of cups, find the number of tablespoons:
I already found that 20 tablespoons is 1 1/4 cups. So for 28 tablespoons I need an additional 8 tablespoons, or an additional 1/2 cup. 1 1/4+1/2=1 3/4, so 28 tablespoons gets him 1 3/4 cups. (Alternatively, we might say that 1 tablespoon is 1/16 cups. 1/16×28=28/16, which we can rewrite as 1 12/16 or 1 3/4.)
I notice that to convert from tablespoons to cups, I always divide by 16. 6÷16=6/16, which we can write as 1 3/8. (Alternatively, 1 tablespoon is 1/16 cups. 1/16×6=6/16, which we can rewrite as 1 3/8.)
Step-by-step explanation:
Sense the two triangles are congruent you would use CPCTC.
The general form of a polynomial is: x² + bx + c = 0. Substituting the roots,
3² + b(3) + c = 0
3b + c = -9 --> eqn 1
(5 + √5)² + (5 +√5)(b) + c = 0
(5+√5)b + c = -30-10√5 --> eqn 2
Solving both equations simultaneously by subtracting eqn 2 from eqn 1,
(-2 - √5)b = 21 + 10√5
b = -8 - √5
Using eqn 1,
3(-8 - √5) + c = -9
-24 - 3√5 + c = -9
c = -9 + 24 + 3√5
c = 15 + 3√5
Hence, the polynomial is: <em>f(x) = x² + (-8 - √5)x + (15 + 3√5)</em>.